Estudio de factibilidad para la creación de una empresa que se dedique a la producción y comercialización de tofu o queso a base de soya en la ciudad de Quevedo, año 2010 - Arguello Palma, Diana Mariuxi (2012)
Q'Soya is a company that aims to offer citizens a high-protein foodstuff, helping to improve the dietary habits of the population. It specializes in the production and marketing of soy-based cheese. The study of market surveys to citizenship quevedeña reveals that you there is a high degree of acceptance of the product and also determines the variables necessary to meet the expectations of consumers, after this analysis is that the producer - trading company will have great market opportunity because there is another company with activities for purposes within the city. By projecting is succeeded in establishing the future demand for the product, which considering the factors affecting the determination of the size of a project was established that the company will cover 7% of the annual unmet demand, what production would be 28.966 lbs.de soy cheese a year... Analyzing the technical study was determined the size and location of the plant, operational processes and resources that will be used to start up project, in addition to the design of the organizational structure of the company producer and marketer of soy cheese. Defined the social reason, designed the logo and slogan, which will reinforce the brand and help that is quickly and easily recognized. To settle over the mission, vision, corporate values, pricing and selection of channels of distribution of the product offered. With the implementation of the studied economic estimated costs, expenses and investment of assets necessary to carry out the project, as well as the income that will be generated by the implementation of sales. And through its analysis establishes that for the implementation of the project is required $13.125,09 of investment, it will be financed with own resources which will be allocated for the investment of fixed assets and capital. By analyzing the financial indices of the project, giving as a result $58.432,45 of the VAN (net present value), 110% IRR (internal rate of return) higher than the interest rate on the market, a benefit/cost ratio of $1.45 and the investment recovery time will be at end of the first year of operation, is considered its feasibility. Determines the financial viability of the project through the analysis of the variables that determine its long-term profitability and are encouraged to the performance of the contract, contributing in this way to the socio-economic development of the city and region.